Integration of water, sanitation, and hygiene for the prevention and control of neglected tropical diseases: a rationale for inter-sectoral collaboration. - Matthew C Freeman; Stephanie Ogden; Julie Jacobson; Daniel Abbott; David G Addiss; Asrat G Amnie; Colin Beckwith; Sandy Cairncross; Rafael Callejas; Jack M Colford; Paul M Emerson; Alan Fenwick; et al. (Public Library of Science (PLoS), 2013)
Improvements of water, sanitation, and hygiene (WASH) infrastructure and appropriate health-seeking behavior are necessary for achieving sustained control, elimination, or eradication of many neglected tropical diseases (NTDs). Indeed, the global strategies to fight NTDs include provision of WASH, but few programs have specific WASH targets and approaches. Collaboration between disease control programs and stakeholders in WASH is a critical next step. A group of stakeholders from the NTD control, child health, and WASH sectors convened in late 2012 to discuss opportunities for, and barriers to, collaboration. The group agreed on a common vision, namely "Disease-free communities that have adequate and equitable access to water and sanitation, and that practice good hygiene." Four key areas of collaboration were identified, including (i) advocacy, policy, and communication; (ii) capacity building and training; (iii) mapping, data collection, and monitoring; and (iv) research. We discuss strategic opportunities and ways forward for enhanced collaboration between the WASH and the NTD sectors.